Compositional and Functional Differences in the Human Gut Microbiome Correlate with Clinical Outcome following Infection with Wild-Type Salmonella enterica Serovar Typhi - Yan Zhang (American Society for Microbiology, 2018)
ABSTRACT Insights into disease susceptibility as well as the efficacy of vaccines against typhoid and other enteric pathogens may be informed by better understanding the relationship between the effector immune response and the gut microbiota. In the present study, we characterized the composition (16S rRNA gene profiling) and function (RNA sequencing [RNA-seq]) of the gut microbiota following immunization and subsequent exposure to wild-type Salmonella enterica serovar Typhi in a human challenge model to further investigate the central hypothesis that clinical outcomes may be linked to the gut microbiota. Metatranscriptome analysis of longitudinal stool samples collected from study subjects revealed two stable patterns of gene expression for the human gut microbiota, dominated by transcripts from either Methanobrevibacter or a diverse representation of genera in the Firmicutes phylum. Immunization with one of two live oral attenuated vaccines against S. Typhi had minimal effects on the composition or function of the gut microbiota. It was observed that subjects harboring the methanogen-dominated transcriptome community at baseline displayed a lower risk of developing symptoms of typhoid following challenge with wild-type S. Typhi. Furthermore, genes encoding antioxidant proteins, metal homeostasis and transport proteins, and heat shock proteins were expressed at a higher level at baseline or after challenge with S. Typhi in subjects who did not develop symptoms of typhoid. These data suggest that functional differences relating to redox potential and ion homeostasis in the gut microbiota may impact clinical outcomes following exposure to wild-type S. Typhi. IMPORTANCE S. Typhi is a significant cause of systemic febrile morbidity in settings with poor sanitation and limited access to clean water. It has been demonstrated that the human gut microbiota can influence mucosal immune responses, but there is little information available on the impact of the human gut microbiota on clinical outcomes following exposure to enteric pathogens. Here, we describe differences in the composition and function of the gut microbiota in healthy adult volunteers enrolled in a typhoid vaccine trial and report that these differences are associated with host susceptibility to or protection from typhoid after challenge with wild-type S. Typhi. Our observations have important implications in interpreting the efficacy of oral attenuated vaccines against enteric pathogens in diverse populations.